Cosmic ray showers angular perspective - Terio, Rosemarie M. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2000)
Angular Flux Distribution of Cosmic rays is measured using two identical plastic scintillators of dimensions 100 x 10 x 1.0 cm3 each coupled optically to a photomultiplier tubes. The two scintillation counters are mounted on an auxiliary wooden structure that is bilaterally constrained to rotate through angles0°, -31°, -45°, -60°, -75°, -85°, 29°, 43°, 55°, 77°, 85°, and 90°. One of the counters forms the exterior layer and extends parallel to the other detector that forms the interior layer at a separation distance of 1.5 m. Signals detected from both detectors at a particular angular position are channeled to the Nuclear Instrumentation Modules (NIMs) for discrimination and counting of coincidences. Standard statistical methods of data analysis are used to calculate the mean and corresponding uncertainties of cosmic - ray flux measurements in every angular displacement of the detector assembly. Results show that the angular flux distribution as measured at the MSU-IIT HEP Laboratory is very nearly proportional to the square of the cosine of the zenith angle.